How can Science help with the Impacts of Climate Change in the Future? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
The exciting 2-way flow of information that the new partnerships are allowing will hopefully help research better its work. Interview with Phil Thornton (CCAFS/ILRI). Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya